2021
DOI: 10.3389/fpsyg.2021.740569
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Coping Strategies of Different Generations of Students Starting University

Abstract: Introduction: Coping strategies and adaptation skills are key features in successfully adjusting to university challenges. Coping skills are an essential part of the Psychological immune system, which leads to successful adaptation. Due to COVID-19 most universities have changed their face-to-face teaching for online education. Nevertheless, there is little concrete empirical evidence on how this generation of students with the ongoing impacts of disruptive changes can cope with it. Colleges and universities n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
2
9
0
1
Order By: Relevance
“…Overall, the results of the present study confirm and extend previous research, by highlighting the interplay between resilience and adaptive coping strategies, as well as by identifying through participants’ direct narratives the intrapersonal and interpersonal protective factors mitigating the negative psychological consequences of the COVID-19 outbreak [ 58 , 59 , 60 , 61 ]. More specifically, highly resilient students seemed to adopt more adaptive coping strategies, such as identifying positive aspects in a negative condition, a reappraisal strategy defined as benefit finding [ 62 ].…”
Section: Discussionsupporting
confidence: 88%
“…Overall, the results of the present study confirm and extend previous research, by highlighting the interplay between resilience and adaptive coping strategies, as well as by identifying through participants’ direct narratives the intrapersonal and interpersonal protective factors mitigating the negative psychological consequences of the COVID-19 outbreak [ 58 , 59 , 60 , 61 ]. More specifically, highly resilient students seemed to adopt more adaptive coping strategies, such as identifying positive aspects in a negative condition, a reappraisal strategy defined as benefit finding [ 62 ].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, in [18], recordings were reported as a useful resource for re-watching portions of a lecture, especially in mathematics courses, where lessons are often broken down by concepts using specific examples; • a positive attitude of students. We agree with Takács et al [11], who found that students were capable of effectively adapting to the virtual teaching modality. They recently explored the characteristics and changes in coping skills of university students in three age groups.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, students entering tertiary education are expected to have much more experience and coping skills than students at lower education levels. Coping strategies and adaptation skills are key to successfully adjusting to university challenges [11]. One might therefore expect that there would be fewer effects on academic achievement at the university level compared to the primary and secondary education levels.…”
Section: Introductionmentioning
confidence: 99%
“…It may originate from a situation where one sexual partner comes into the sexual relationship already infected, or becomes infected later in life [5][6][7][8][9][10]. HIV serodiscordant is recognized as a priority for HIV prevention due to the risk of transmitting the virus to the HIVnegative partner [9][10][11][12][13][14][15]. Improvements in the effectiveness and availability of HIV treatment in recent years have enabled HIV-positive individuals to live longer and healthier [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in the effectiveness and availability of HIV treatment in recent years have enabled HIV-positive individuals to live longer and healthier [16][17][18][19][20]. However, this treatment has also contributed to an increasing number of HIV serodiscordant couples and an increased rate of HIV transmission [14].…”
Section: Introductionmentioning
confidence: 99%